A Critical Discourse Analysis of E-Paper 'KPU chief rebuffs allegations of bias during VP debate" in Jakarta Post - neneng sri lestari; Yunita Sari Adelina; Fernando De Napoli Marpaung; Donny Adiatmana Ginting (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2024)
This research employs critical discourse analysis (CDA) to examine a news article titled "KPU Chief Rebuffs Allegations of Bias during VP Debate" from the Jakarta Post, focusing on the transition from print to online media or E-Paper. In this research, the two main methods used to collect data are documentation via the Jakarta Post e-paper news page and content review. This approach provides the advantage of exploring information in depth and comprehensively related to the phenomenon or event that is the focus of the research. Utilizing Teun A. van Dijk's CDA framework, the analysis encompasses macro, superstructure, and micro structures. The macro-structural analysis reveals the social and political context, identifying social groups and emphasizing narrative importance. The critical discourse superstructure analysis delves into linguistic patterns, representations of power, and strategic language use. Finally, the micro-structural analysis explores word choice, grammar, writing style, and sentence structure to understand how language constructs arguments and responds to accusations. Through these lenses, the study provides a comprehensive understanding of how the news shapes and reflects social and political dynamics, contributing valuable insights into media discourse surrounding political events in Indonesia.